The diameter of products of finite simple groups - Dona, Daniele (Ars mathematica contemporanea, 2022)
Following partially a suggestion by Pyber, we prove that the diameter of a product of non-abelian finite simple groups is bounded linearly by the maximum diameter of its factors. For completeness, we include the case of abelian factors and give explicit constants in all bounds.
Keywords: complete signed graph; diameter; enostavne končne grupe; finite simple groups; premer